AI-Based Learning Model to Increase Sharia Financial Literacy at the Al-Fikh Orchard Malaysia Education Institute - Rahmayati, Rahmayati (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
In Malaysia, sharia financial literacy is a very important issue, especially among educational institutions that are oriented towards Islamic education, such as the Al-Fikh Orchard Educational Institution. In this case, the application of an AI-based interactive learning model can be an innovative solution that not only increases students' interest in learning but also deepens their understanding of sharia financial literacy. By utilizing AI technology, especially through platforms such as Quizizz AI, the learning process can be tailored to individual student needs, provide more precise evaluations, and create a more engaging and interactive learning experience. The aim of this research is to provide an AI-based learning model to increase sharia financial literacy at the Al-Fikh Orchard Malaysia Education Institute, by utilizing platforms such as Quizizz AI which can help develop interactive learning and evaluation modules. It is hoped that this research can make a significant contribution in increasing learning effectiveness and can be adapted by other educational institutions. The stages of this research method start from identifying the problem of low sharia financial literacy at the Al-Fikh Orchard Malaysia Education Institute, then collecting literature studies and previous research regarding the research theme, then after identification, problem classification and problem focus, research is carried out by creating a Focus Group Discussion (FGD) with stakeholders from the Al-Fikh Orchard Malaysia Education Institute.